Fasciolosis in Ruminants - Nadia Mohammed; Wassan Alobaidii; Shahad Ali (Basrah Journal of Veterinary Research)
Fasciolosis is disease caused by a liver worm called Fasciola  is one of the dangerous parasites that affects the livestock specially sheep are wide spread in many countries of the world including some Arab countries. This worm attacks animals such as cows, buffaloes, camels, horses, donkeys, sheep, goats and rabbits that feed on grass and plants. The worms inhabit the bile ducts in the liver of humans and animals and they multiply and spread in all tissues causing many damages and risks to public health and great losses in animal production Therefore we will present the detailed aspects of this disease its classification and description of species symptoms methods of infection life cycle, epidemiology pathological diagnosis of prevention